Mengenal Jejak Peninggalan Prabu Siliwangi di Kampung Adat Urug - Firman Syah (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2019)
The research activities carried out are of an inductive qualitative nature located in Urug Indigenous Village, Kiara Pandak Village, Sukajaya District, Bogor Regency, West Java. The informant chosen was Abah Ukat Raja Aya as a traditional figure. Primary data collected directly from informants in the form of questionnaires for direct interviews and supplemented by secondary data from literature studies.As a trace of the legacy of King Siliwangi, Urug Indigenous Village is one of the areas included in the category of cultural tourism destinations, namely the Ministry of Education and Culture with Cultural Institution Number: LK20181124000302 with the proposer being Abah Ukat Raja Aya. For this reason, this research was conducted to find out the history of the birth of the Urug Indigenous Village and the cultural model preserved by the Urug Indigenous Village.The results show that the history of the birth of the Urug Indigenous Village is derived from the word 'teacher', which is an acronym form of digugu and imitated meaning can be trusted and made a role model. As for the journey the origin of the teacher's name because it was deliberately hidden or disguised so as not to be known, the letter ‘g’ moved back to Urug. The cultural model preserved by the First Urug Indigenous Village in terms of hereditary leadership, the existence of a large house as a center of authority for traditional leadership, and the lives of people who have a livelihood from planting to harvesting rice.